Fuel types and use in late Western Zhou (877 – 771 BCE) industrial contexts in Northwest China - Zhikun Ma; Shu Liu; Xuan Yi; Liya Tang; Zhongyang Fu; Di Wang; Qingli Sun (Scientific Reports, 2024)
Abstract To date, the types of fuels used in pottery kilns during the Western Zhou Dynasty have not been adequately addressed. Samples from updraft kilns and semi-downdraft kilns at the Fengjing site, the capital in the late Western Zhou period, were selected for analysis. Through phytolith and wood charcoal analysis, various grasses mainly Panicoideae, Pooideae, and Eragrostidoideae, as well as millet, rice, and wheat crops were identified. Additionally, wood primarily from trees of the Quercus, Ulmus, and Liquidambar taxa was found. These findings suggest that different pottery kilns used similar fuels, demonstrating a broad-spectrum rather than specialized fuel utilization during the Zhou period.